Diseño y planificación de la implementación de un manual de valoración de cargos para las empresas Samper Head Hunting y Kmeyo - Burbano Terneus, María Fernanda (2015)
This work whose theme is "Design and implementation planning of the valuation manual of positions for the Companies SamperHH and Kmeyo” focuses on structuring the methodological basis of information collecting and position’s analysis to develop subsystems of compensations, career plans, etc. Which actually the companies does not have. This way the companies can build, measure and improve their internal structure per se. The companies Samper Head Hunting and Kmeyo are dedicated to provide services in Consulting and Talent Consulting for companies in various sectors in the labour market. Their products are: Selection, Hunting, Assessment Center, Performance Evaluation, Career Plan, among others. Their main goal is to be competitive in the national and international labour market through High Quality service. It is therefore essential to strengthen the internal structure of the companies by creating, compensation systems, work environment, career, policies, and descriptive plan, among others. Meaningful that people are the main resource of the company for their knowledge, skills and attitudes in the performance of their duties; is critical to create some guidelines which conducted professionally can result in productivity. When performing an analysis on existing methods of valuation was concluded that the methodology “Scales and Profiles of valuation charges” is appropriate to apply in the business, as it allows objectively classify each position, knowing the entirety of it, and analyzing the complexity and demands required, to finally locate them in the resulting wage levels.